Acculturative Stress and Postpartum Depressive Symptoms among Immigrant Arab American Couples. Issue 2 (March 2022) - Khalil, Dalia; Giurgescu, Carmen; Misra, Dawn P.; Javanbakht, Arash; Templin, Thomas; Jenuwine, Elizabeth
Abstract: Purpose: The purpose of this study was to examine the relationships between acculturative stress, perceived stress, social support, and postpartum depression (PPD) symptoms among immigrant Arab American couples. Methods: Using a cross-sectional design, 30 Arab American immigrant couples were enrolled. During home visits, couples completed the demographic information, the Multi-Dimensional Acculturative Stress Inventory, Perceived Stress, the Multidimensional Scale of Perceived Social Support among Arab Women, and the Edinburgh Postnatal Depression Scale. Data were analyzed using bivariate linear regression and Pearson correlation. Results: In bivariate regressions, paternal and maternal acculturative stress was moderately associated with maternal PPD symptoms ( r = .39, and .46, respectively; p < .05). Maternal perceived stress ( r = .70, P < .01) was strongly associated with PPD and maternal perceived social support was moderately associated with PPD ( r = -.42, p < .05). Maternal and paternal acculturative stress was strongly correlated ( r = .61, p < .001). Conclusion: Couple's acculturative stress and mother's perceived stress were positively associated with mother's PPD symptoms. Our findings suggest the need to develop a culturally appropriate procedure to assess couple's stress that may affect immigrant women at high risk for PPD. Abstract : Approximately 3.5 million Arab Americans live in the United States, yet they are largely absent from health research on family mental health and infant outcomes, in part due to the classification of Arab Americans within the U.S. racial schema as "White" which makes them invisible as a minority group. In this study, immigrant Arab American couples are asked about their stress during postpartum and new parenting. Relationships between acculturative stress and postpartum depression are explored.